MERR APEX-seq protocol for profiling the subcellular nascent transcriptome in mammalian cells - Ran Li; Peng Zou (STAR Protocols, 2023)
Summary: Knowledge about the spatial organization of RNAs in eukaryotic cells is crucial for understanding their functions. Here, we present a detailed MERR APEX-seq protocol to achieve spatiotemporally resolved mapping of the subcellular transcriptome in cultured mammalian cells. This protocol provides detailed description of constructing cell lines stably expressing APEX2, immunofluorescence characterization, MERR APEX labeling, enrichment of biotinylated RNA, library construction and high-throughput sequencing, and MERR APEX-seq data analysis.For complete details on the use and execution of this protocol, please refer to Li et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.